Our possessions, our selves: Domains of self‐worth and the possession–self link - Ferraro, Rosellina; Escalas, Jennifer Edson; Bettman, James R. (Journal of Consumer Psychology, 2011)
AbstractThe extent to which a possession is linked to self is a critical determinant of whether a possession elicits grief if lost. We propose a framework for understanding the formation of the possession–self link, arguing that a possession's ability to represent the important domains on which a person bases her self‐worth affects the possession–self link. We also show that dispositional tendencies to incorporate possessions into the self moderate this relationship, while the monetary value of the possession does not affect the strength of the possession–self link.